Range : How generalists triumph in a specialized world - Epstein, David (Macmillan, 2019)
Range is the ground-breaking and exhilarating exploration into how to be successful in the 21st Century, from David Epstein the acclaimed author of The Sports Gene. What if everything you have been taught about how to succeed in life was wrong? From the '10,000 hours rule' to the power of Tiger parenting, we have been taught that success in any field requires early specialization and many hours of deliberate practice. And, worse, that if you dabble or delay, you'll never catch up with those who got a head start. This is completely wrong. In this landmark book, David Epstein shows that the way to excel is by sampling widely, gaining a breadth of experiences, taking detours, experimenting relentlessly, juggling many interests - in other words, by developing range. Studying the world's most successful athletes, artists, musicians, inventors, and scientists Epstein discovered that in most fields - especially those that are complex and unpredictable - generalists, not specialists, are primed to excel. They are also more creative, more agile, and able to make connections their more specialized peers can't see. Range proves that by spreading your knowledge across multiple domains is the key to success rather than deepening their knowledge in a single area.